Investigation on the connection forces of shear keys in skewed bridges during earthquakes. (1st September 2019) - Wu, Suiwen
Highlights: Shear key forces in skew bridges can be dominant at acute corners if gap is closed. The design connection force in AASHTO could be inadequate in low seismic zone. It is recommended to increase gap to reduce shear key force in low seismic zone. Longitudinal motion should be considered to compute the shear key forces. A SM was developed to estimate the maximum shear key forces in skew bridges. Abstract: One of the prevalent seismic damage modes of skewed bridges is that the shear keys and/or other transverse retainers at the acute corners suffer severer damages than those at the obtuse corners. In practice, the retainers are usually designed and detailed as structural fuses to protect the substructure and foundation in high seismic zones. However, in low seismic zone, such as seismic zone 1 in AASHTO, they are designed elastic. In this paper, a parameter study was conducted to: (1) investigate the distribution of forces among the shear keys in skewed bridges and (2) evaluate AASHTO's provisions for the minimum connection force of shear keys in low seismic zone. Parameters of interest include skew angle and expansion gap size. An experimentally validated numerical model was employed to model the prototype bridges with exterior shear keys. Nonlinear response history analysis was performed. The results show that when the longitudinal gap is closed for small to moderate gaps, the forces in the keys at the acute corners can be much higher than those at the obtuse corners. This is most likely to occur since the keys should resist the transverse loading along with the impact and friction forces at the abutment-deck interface caused by longitudinal motion. These higher forces of the keys at the acute corners could exceed AASHTO's limit in low seismic zone. To reduce the forces in the keys, it is recommended that the gap be increased in size to avoid abutment pounding, which is an affordable solution in low seismic zone since the increase is expected to be small. Further, a Simplified Method is developed to estimate the maximum connection forces of skew bridges in low seismic zone. Good agreement was obtained between the Simplified Method and the FEM model. Therefore, the Simplified Method may be used for the preliminary design of shear keys.